Leaf thickness and density drive the responsiveness of photosynthesis to air temperature in Mediterranean species according to their leaf habitus. (March 2018) - Gratani, Loretta; Varone, Laura; Crescente, Maria Fiore; Catoni, Rosangela; Ricotta, Carlo; Puglielli, Giacomo
Abstract: The responsiveness of net photosynthetic rate (Aa ) to mean monthly air temperature (TM ) of eight Mediterranean evergreen species was investigated by analyzing the inter-annual changes in leaf mass area (LMA), leaf tissue density (LTD) and leaf thickness (LT). We wanted to test if species leaf habitus affected this response. To hit the goal, a multi-year dataset from our previously published papers was used. The inter-annual variability in LMA, LTD and LT was assessed by their coefficients of variation (CVs). Aa sensitivity to TM (SAa ) was quantified by the slope of the species-specific relationships Aa -TM . A Principal Component Analysis (PC) was carried to identify the leaf morphological variation patterns across species. SAa was affected by the coordination of LTD and LT across species and this coordination depended on leaf habitus. The relationship between CVs and SAa revealed that only evergreen sclerophyllous with a longer leaf life-span rely on the inter-annual changes in LTD and LT to modulate their SAa . Overall, the results showed that the inter-annual LTD and LT variability affected the responsiveness of net photosynthetic rate of the selected species according to their leaf habitus. Highlights: Leaf thickness and density were unrelated across species depending on leaf habitus. Climatic variability affected the coordination between leaf thickness and density. C. incanus was an outlier compared to other studied species.